Developing Needs Analysis of Critical Literacy Models for Teaching EFL Reading Class - Diyah Ayu Rizqiani; Syafriani Novitri (UIR Press, 2023)
Critical literacy models have been integrated into learning process in the English-speaking countries such as Australia, New Zealand, America, England, and some Europian countriea. As matter of fact, the critical literacy model used particularly for teaching reading classess is rarely found, especially the model which fits with the characteristics of EFL students. This study aims to explore the needs analysis development of critical literacy model for teaching reading in EFL reading class. This research adapted the Four D model which consists of four steps; defining, designing, developing, and disseminating. The results revealed the following. First, in defining, the researcher conducted preliminary study in English Language Education Study Program in three universities in Yogyakarta which was meant to analyze the students’ problems in the real setting. Second, the researcher created the prototype of the needs analysis in accordance with the results of the preliminary study. Third, the researcher validated the needs analysis to the two experts and conducted field testing to evaluate the validity of the questionnaire. The results of the needs analysis validation process show that the questionnaire is feasible (87.5 %) to assess the students’ needs of critical literacy model. Furthermore, in order to evaluate the practicality of the questionnaire, the researcher conducted a preliminary field testing to 27 students of English Language Education Study Program in a private university in Yogyakarta. In conclusion, the results of the needs analysis become the basis to develop a critical literacy model which is used for teaching EFL reading classes.